(untitled) (Research, Society and Development, 2020)
Considering that Project Based Learning aims to structure the resolution of real problems related to the creation of services or products, the present study aimed to base this methodology to analyze the competencies of Physical Therapy students in the development of products through an self-assessment instrument. This is a descriptive exploratory study, approved by the Research Ethics Committee (opinion no. 3.497.251) with the enrollment of 29 undergraduate students in Physical Therapy at the State University of Pará (UEPA). The skill assessment tool was adapted from the EABP / EaD Self-Assessment Scale and made available through the Googleforms tool. The total average skill index calculated by the instrument was 86,86%. The competencies with the best evaluation mean by the students were problem analysis (3,69) and identification of user needs (3,72). On the other hand, the skills with the lowest average self-assessment were creativity (3,26) and representation ability (2,45). There is a better evaluation of competences related to the analysis of problems and user needs, compared to competences related to the creative conception of projects and forms of representation.